Hepatopulmonary Syndrome in an Adolescent With Insidious Hypoxia and Small Intrahepatic Portal Venous Shunts: Posttransplant Benefit From Sildenafil. (December 2020) - Slowik, Voytek; Hildreth, Amber; Pacheco, M Cristina; Finn, Laura S; King, Jeremy; Shivaram, Giridhar; Files, Matthew; Hsu, Evelyn K; Horslen, Simon
We report a patient without known preexisting liver disease who presented with hepatopulmonary syndrome (HPS) due to aberrant intrahepatic portal venous development leading to portosystemic shunting. Liver transplantation resulted in resolution of portal hypertension and HPS and sildenafil was safely tolerated in the treatment of persistent fatigue and hypoxemia. Twelve months later, patient has normal allograft function and has returned to normal activity.